Exclusive Image Gallery on Human Spinal Cord Regeneration-Clinical Image-49 - Giselher Schalow (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2019)
Improvement of free walking on treadmill of the 10-year-old patient Nefeli with a SCI. At the beginning a walking speed of 2.5km/h was only possible, later on a speed of 4km/h became possible. The patient walked without shoes to have a better sensory input and in this way a higher stability, which was the limiting factor of continuous walking.